1994
DOI: 10.1246/cl.1994.539
|View full text |Cite
|
Sign up to set email alerts
|

N,N,N′,N′-Tetramethylazodicarboxamide (TMAD), A New Versatile Reagent for Mitsunobu Reaction. Its Application to Synthesis of Secondary Amines

Abstract: N,N,N′,N′-Tetramethylazodicarboxamide, TMAD, was found to be more versatile in the Mitsunobu reaction than traditional diethyl azodicarboxylate or recently developed 1,1′-(azodicarbonyl)dipiperidine, when used in combination with tributylphosphine in benzene. The usefulness of the reagent was demonstrated by the highly efficient two-step synthesis of benzylcrotylamine from N-benzyltrifluoroacetamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(61 citation statements)
references
References 8 publications
1
59
0
Order By: Relevance
“…We recently reported that intramolecular Mitsunobu reaction of a diol 14ab 17) (1 : 1 diastereomeric mixture), which was prepared starting from (R)-benzyloxymethyl-g-butyrolactone (12), 18) with N,N,NЉ,NЉ-tetramethylazodicarboxamide (TMAD) 19) and Bu 3 P followed by desilylation affords trans-and cis-cyclization products 15 (47%, 9% ee) and 16 (53%, 20% ee) with low optical purities (Chart 2). The low optical purities were attributed to indistinguishable activities between two hydroxy groups of 14ab.…”
Section: Synthesis Of Imifuraminementioning
confidence: 99%
“…We recently reported that intramolecular Mitsunobu reaction of a diol 14ab 17) (1 : 1 diastereomeric mixture), which was prepared starting from (R)-benzyloxymethyl-g-butyrolactone (12), 18) with N,N,NЉ,NЉ-tetramethylazodicarboxamide (TMAD) 19) and Bu 3 P followed by desilylation affords trans-and cis-cyclization products 15 (47%, 9% ee) and 16 (53%, 20% ee) with low optical purities (Chart 2). The low optical purities were attributed to indistinguishable activities between two hydroxy groups of 14ab.…”
Section: Synthesis Of Imifuraminementioning
confidence: 99%
“…The more recently described Tsunoda conditions, employing tributylphosphane (TBP) and 1,1Ј-(azodicarbonyl)dipiperidide (ADDP), [29] were reported to give excellent yields in the alkylation of 2-nitrobenzenesulfonamides in the synthesis of polyamine toxins on solid phase. [30] Consequently, this reagent combination was selected, along with the less hindered N,N,NЈ,NЈ-tetramethylazodicarboxamide (TMAD) [31] and trimethylphosphane (TMP) [32,33] for our investigation of the alkylation of 2-nitrobenzenesulfonamides (Ns-amides) with secondary alcohols. The Ns group is convenient in both solid and solution phase syntheses, because it is readily removed under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Tsunoda et al obtained 34% and 40% yields in the alkylation of 2-octanol with N-methyl-p-toluenesulfonamide using ADDP-TBP and TMAD-TBP, respectively. [31] …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported an efficient method for the formation of ribofuranosyl C-nucleosides or THFs with a fivemembered ring via a diazafulvene intermediate (like 8), which involved intramolecular cyclodehydration of the corresponding diols using N,N,NЈ,NЈ-tetramethylazodicarboxamide (TMAD) 32) and Bu 3 P. 31) Therefore, we first attempted treatment of 7 with TMAD (1.5 eq) and Bu 3 P (1.5 eq) at rt in benzene for 17 h, followed by tert-butoxycarbonylation to facilitate isolation, but N im -Boc-THP intermediate 10 was produced in only 7% yield (Table 1, entry 1). Use of 3 equivalents each of TMAD and Bu 3 P under benzene reflux somewhat improved the yield to 43% (entry 2).…”
mentioning
confidence: 99%